The south China sea disputes : formula for a paradigm shift? - Robert C. Beckman (2014)
China could trigger a paradigm shift in disputes in the South China Sea if it were to issue charts indicating the outer limit of its exclusive economic zone (EEZ) claims from the islands over which it claims sovereignty. A full effect ‘equidistance line’ from the largest islands towards the surrounding coats would create a large area of overlap between the EEZ claims of the ASAN claimants and the EEZ claim of China from the disputed islands. This could lead to possible provisional arrangement of a practical nature, including joint development zones, in the areas of overlapping claims.